Hermite-Hadamard type inequalities for functions whose $n^{th}$ order of derivatives are $s$-convex in the second sense - Meftah, Badreddine; Merad, Meriem (Revista MATUA, 2017)
In this paper, we establish some Hermite-Hadamard type inequalities for functions whose $n^{th}$ dirivatives are $s$-convex in the second sense. Several known results are derived . Applications to special means are also given.